1998
DOI: 10.1677/joe.0.1560441
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant somatolactin as a stable and bioactive protein in a cell culture bioassay: development and validation of a sensitive and reproducible radioimmunoassay

Abstract: A recombinant somatolactin (SL) obtained by cloning and expression of sole SL cDNA was analyzed and used to develop a sensitive and specific RIA. In contrast to native proteins, which tend to dimerize and aggregate immediately after pituitary isolation, the majority of recombinant sole SL (rsSL) remained as a monomeric protein after long-term storage, as shown by size exclusion chromatography and Western blot. Using rsSL as a tracer and standard in the RIA, the minimum detectable dose and the midrange (ED 50 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…1). Generally, hormones activate receptors in a dose-dependent manner, and a dose-response curve of SLa has been known to become bell shaped (Calduch-Giner et al, 1998); i.e., over-dosing inhibits activation (dimerization) of the receptor. We found that SLR (and also GHR) is transcribed at a similar level between ci and Actb-SLa:GFP in all organs examined (Fig.…”
Section: Effects Of Sla On Lipid Storage and Cortisol Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Generally, hormones activate receptors in a dose-dependent manner, and a dose-response curve of SLa has been known to become bell shaped (Calduch-Giner et al, 1998); i.e., over-dosing inhibits activation (dimerization) of the receptor. We found that SLR (and also GHR) is transcribed at a similar level between ci and Actb-SLa:GFP in all organs examined (Fig.…”
Section: Effects Of Sla On Lipid Storage and Cortisol Secretionmentioning
confidence: 99%
“…Although SL may (or may not; as exemplified by the above conflicting evidence between species) have important functions during these circumstances, its direct effects on the body remain unknown from these observations. Several in-vitro/vivo experiments using purified/recombinant SL revealed its physiological activities in steroidogenesis (Planas et al, 1992), phosphate transport (Lu et al, 1995), melanosome aggregation (Zhu and Thomas, 1997), phagocyte activation (Calduch-Giner et al, 1998; but see Sakai et al, 1996), lipolysis (Vega-Rubín de Celis et al, 2003), etc. However, because the effects are often weak despite the rather high doses of SL (N100 ng/ml), it is still unclear whether or not endogenous SL (∼ 20 ng/ml in the plasma; Rand-Weaver et al 1995;Zhu and Thomas 1996;Diez et al, 2007) actually plays significant roles in these activities.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to GH and PRL, SL is a member of the class I cytokines with the typical feature of four ␣-helixes arranged in an up-up-down-down topography (16). To date, SL has been associated with diverse functions in fish models, including reproduction (29,36), stress (21), lipid metabolism (40), background adaptation (53,55), phosphate transport (25), melanosome aggregation (28,54), and immune responses (4). Although most of the above-mentioned functions attributed to SL were based on correlational studies, the functional role of SL in color presentation has been unequivocally demonstrated in fish species.…”
mentioning
confidence: 99%
“…Researchers have isolated SLs from many fish species and detected up-and downregulation of its expression during variable physiological processes (see references in Fukada et al 2005). Experiments using recombinant proteins of SLs show certain biological activities in vitro and in vivo (Lu et al 1995;Calduch-Giner et al 1998;Vega-Rubin de Celis et al 2003). However, none has been supported by clear and direct evidence explaining the mechanisms or actions of target cells, tissues, and organs of SLs.…”
mentioning
confidence: 99%